Pathogenesis of aleutian disease of mink: identification of nonpersistent infections. - Larsen, A E (1975)
Aleutian disease virus usually produces a persistent infection and progressive immune comples disease in mink of the Aleutian genotype. Study of Aleutian disease virus infection in non-Aleutian mink showed that about one-quarter developed nonpersistent infections by the virus, and that the nonpersistence was not genetically determined by the host. The nonpersistently infected mink developed only a transient elevation of serum gamma globulin, and much lower specific Aleutian disease virus antibody titers than persistently infected mink. No lesions were found in the nonpersistently infected mink.